POLEMIK PESANGON DALAM PERSPEKTIF UU OMNIBUS LAW - Pakpahan, Elvira Fitriyani; Daeli, Nilam Permata; Evelyne; Heriyanti (Arena Hukum, 2023)
This paper aims to assist in providing understanding to both entrepreneurs and workers or workers, as well as the general public that the Omnibus Law which is considered detrimental to each party was formed by the government with several other alternatives that can be used to deal with problems that arise in the scope of work, and can help the country in improving its economy, one of which is by attracting the attention of foreign investors to be interested in investing in this country. This research is uses qualitative methods through qualitative descriptive procedures. The Omnibus Law itself can be good news for the general public because it can be a solution to severance pay cases for workers who are victims of termination of employment.